On the Efficacy of Open Educational Resources: Parametric and Nonparametric Analyses of a University Calculus Class - Delgado, Huimei; Delgado, Michael; Hilton III, John (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2019)
Open educational resources (OER), which are free and openly licensed educational materials, have been a widely discussed topic in response to high textbook costs, the need for more pedagogical flexibility, and inequality in access to educational materials. In this study we examine the efficacy of OER through a quantitative analysis of the impact of OER on student final exam performance in a large calculus course. Our dataset affords us a relatively large sample size, allows us to classify students in both treatment and control groups, and includes a variety of covariates that allow us to control for multiple correlated factors. We estimate causal treatment effects using several econometric approaches. Our study adds the following insights into the research on OER efficacy: (i) OER materials do not, in general, lead to any significant change in student final exam performance; and (ii) OER materials have a significantly positive impact on both international students and Pell Grant eligible students.